Jamaah Wadah Nun, Disiplin, Kebebasan dan Amalan: Refleksi dari Penelitian Lapangan - Arfah Lalang (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2014)
The study of the discipline has been carried out by the experts, one of whom was Foucault, whose his work illustrates the discipline can be formed when a person is bound by rules curbing him/her . He took the example of military institutions or educational institutions as a mode of discipline, that in which there are "power" which regulates all forms of someone behavior. Likewise with Dawud Fasting (puasa) performed by pilgrims Jamaah Wadah Nuun, discipline can be obtained from fasting dawud for the pilgrims. This research is anthropological research that requires down the field to dig up the facts and the involvement of researchers in the congregation Jaamah Wadah Nuun. This research seeks to understand how fasting of dawud put into practice by the congregation as a model of discipline. How to practice fasting of dawud regarded as an obligation of the pilgrims, but not binding, how the image of power relations that exist in the pilgrims of Jamaah Wadah Nuun, how the portion of power committed by pilgrims and Murshid, how the pilgrims formed a power in itself and affect its social environment.